Causes of death, survival and risk factors of mortality in Thai patients with early systemic sclerosis: inception cohort study - Suparaporn Wangkaew (2018)
© 2017, Springer-Verlag GmbH Germany. Inception cohort study regarding the causes of death and risk factors for mortality in patients with early systemic sclerosis (SSc), especially diffuse SSc (dcSSc) has not been well elucidated. Therefore, the aim of our study was to determine the causes of death, survival rates, and risk factors for mortality in Thai patients with early SSc of whom the majority belonged to the dcSSc subset. We used an inception cohort of early-SSc patients seen between January 2010 and August 2014. All patients were evaluated for clinical and laboratory data at the study entry and then every 6 months. A total of 115 patients (68 female, 91 dcSSc) were enrolled. The mean ± SD age at onset, duration of disease, and duration of follow-up were 52.5 ± 8.5 years, 12.3 ± 9.2 months, and 27.5 ± 16.4 months, respectively. During the follow-up, 11(9.6%) SSc patients died. The mortality rate was 4.17 per 100 person-years (95% CI 2.31, 7.53). The leading cause of SSc-related death was dilated cardiomyopathy (27.2%). Infection was the most common cause of non-SSc-related death (18.2%). Survival rates at 1, 2, 3, and 4 years after the study entry were 93, 91, 88, and 88%, respectively. In the multivariate Cox regression analysis, ESR ≥ 40 mm/h [HR 8.65 (95% CI 1.66,45.17)], hemoglobin < 10 mg/dL [HR 4.57 (95% CI 1.14,18.34)], and mRSS [HR 1.09 (95% CI 1.03,1.15)] were independent risk factors for mortality. Our data suggest that dilated cardiomyopathy was the most common SSc-related cause of death in Thai patients with early SSc, of whom majority was dcSSc subset. Elevated ESR, anemia, and increased mRSS predicted poor outcome.